Understanding Roles of Religions in Indian Society (Indian Journal of Social Science and Literature (IJSSL), 2024)
The individuals, belonging to all communities, categories and socio-economic backgrounds have recognized the meaning and significance of religions. The overall living conditions of the individuals are centred on religions. The tasks and activities that are put into operation by the individuals in personal and professional lives are complicated and manageable. Furthermore, these are put into operation in less amount of time or can be more time-consuming, hence, the roles of religions are regarded to be indispensable in preparing the individuals in a satisfactory manner. The individuals in this manner are augmenting information in terms of norms and values. Furthermore, religions impart information to the individuals in differentiating between various types of appropriate and inappropriate factors. These are regarded as the key in putting into operation all types of tasks and activities in a well-organized and disciplined manner. Furthermore, individuals need to be well-informed in terms of traits of morality and ethics. The religions impart information in terms of these traits. In addition, these are regarded as the key in not only putting into operation job duties successfully, but also in developing mutual understanding with others. Therefore, it is of utmost significance for individuals to acquire an efficient understanding of roles of religions in Indian society. The main concepts that are taken into account in this research paper are, understanding the roles of religions in Indian society and advantages of acknowledging roles of religions in Indian society.